Utilization of Banana Stem (Musa paradisiaca L.) as a Raw Ingredient for Chip Production: Consumer Response Analysis and Economic Value Potential - Khosyiati, Nur Evirda; Setiawan, Rizal Justian; Ma'ruf, Khakam; Azizah, Nur; Darmono (Program Studi Teknologi Hasil Pertanian Universitas PGRI Banyuwangi, 2025)
Banana stem or banana pith (Musa paradisiaca L.) is an often underutilized part of the banana plant, despite its high content of dietary fiber and polyphenols. This study aims to process banana stems into flour and use it as a base ingredient for producing chips, as well as to evaluate the product's quality based on sensory aspects and economic feasibility. The research method involves the process of banana stems flour production, mixing it with tapioca flour in various proportions, and conducting organoleptic testing with 22 panelists, consisting of academics and the general public. The results indicate that the optimal formulation is achieved with a 50% banana stem flour and 50% tapioca flour ratio. Quality testing showed that 95.4% of panelists rated the chips as savory with a distinct banana stem flavor, 100% agreed the color was brown and met the standard, 100% found the texture to be crisp and crunchy, and 97% considered the oval shape ideal. From an economic perspective, the production of these chips incurs a cost of IDR 50,000 per batch, with a selling price of IDR 1,500 per package and a net profit of IDR 1,450,000 per month. SWOT analysis and business strategy indicate that banana stem chips have potential for development as a home-based industry product with promising market prospects. In conclusion, the utilization of banana stems as a base ingredient for chips not only provides an innovative food alternative but also offers a competitive economic value.